Neuropsychological indicators of postoperative cognitive dysfunctions after off-pump coronary artery bypass grafting - Antonenko, V.V.; Dubrov, S.O. (Medicni Perspektivi, 2025)
The problem of postoperative cognitive dysfunctions (POCD) becomes more significant with the increase in frequency and expansion of operations in cardiac surgery practice. It’s one of the common clinical complications following anesthesiologic support in cardiac surgery, which can change in a long-term period. POCD is a decrease of cognitive functions after surgery and general anesthesia from the baseline preoperative level. It’s characterized by impairment of attention, concentration, memory, learning and processing of information, verbal, visual and visuospatial deficits. The attention of anesthesiologists and specialists in related specialties is attracted by the medical and social consequences of cognitive disorders, which have a negative impact on the duration of hospitalization, its cost, and the quality of life of patients in the remote postoperative period with an increase in the frequency and duration of incapacity for work, the need for rehabilitation, the financial burden on the patient and his family The aim of our study was to identify neuropsychological indicators of cognitive functions in the short-term and long-term postoperative period in patients with coronary heart disease who underwent off-pump coronary bypass grafting. There were examined 257 patients of 44-78 years old with coronary artery disease, all of them underwent off-pump coronary bypass grafting during period of 2019-2021 years and was hospitalized in the department of Cardiac Surgery at the National scientific center of surgery and transplantation named after O.O. Shalimov, Kyiv, Ukraine. Trail Making Test (TMT) and Mini Mental State Examination (MMSE) were used for cognitive function assessment. This study showed that 47.08% of patients had cognitive dysfunctions after cardiac surgery, which improved in postoperative period after 6 months in 19.01% (n=23) of patients with POCD. Worsening of cognitive performance was observed mainly in older population (65 and older). Geriatric patients had lower cognitive performance and are vulnerable to neurophysiological changes after cardiac surgery, that may be a higher risk of POCD. The results of testing using MMSE and TMT in patients with coronary heart disease who underwent off pump coronary artery bypass grafting revealed that the frequency of POCD with a maximum decrease of cognitive functions was on the 3rd day after surgery with gradual recovery of cognitive functions on 6-8 day. However, in 80.99% of patients with POCD the level of cognitive functions is not recovered in full preoperative score.